Studi Carbon Footprint Dari Aktivitas Rumah Tangga Di Kelurahan Limbungan Baru Kecamatan Rumbai Pesisir Kota Pekanbaru - Okthasia Indra; Aryo Sasmita; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Limbungan Baru is the most populous Sub-District in Rumbai Pesisir District. The high level of density population in Limbungan Baru Sub-District is as one potential contributor of CO2 emissions. The calculation of total energy consumption that generate CO2 emmision was called carbon footprint. The CO2 emissions from the household activities are divided into primary and secondary CO2 emissions. The primary CO2 emissions is resulting from fuel used in households, while the secondary CO2 emissions is resulting from the used of electric household equipment. CO2 emmision were calculated using IPCC method (1996). Total CO2 emissions from household activities in Limbungan Baru Sub-District is 2.194,614 tons CO2/month where primary CO2 emissions amounted to 185,535 tons CO2/month, and secondary CO2 emissions amounted to 2.009,089 tons CO2/month.Keywords: Carbon footprint, CO2 emission, Household, Electricity Energy, Fossil Fuels